Complete remission of metastatic HER2+ oesophagogastric junctional adenocarcinoma under long-term trastuzumab treatment - Gutting, Tobias; Schulte, Nadine; Belle, Sebastian; Betge, Johannes; Härtel, Nicolai; Wilke, Jürgen; Weers, Jürgen; Ebert, Matthias; Zhan, Tianzuo (Journal of gastrointestinal and liver diseases, 2019)
Metastatic gastric cancer (GC) and oesophagogastric junctional (OGJ) adenocarcinoma have a poor clinical outcome with a high worldwide burden of disease. A 65-year old male patient with microcytic anemia was diagnosed with stage IV OGJ adenocarcinoma with multiple liver metastases. Immunohistochemical analysis revealed a high expression of HER2 (3+). Palliative chemotherapy with FLOT (oxaliplatin, 5-fluorouracil, leucovorin and docetaxel) in combination with trastuzumab was initiated. Due to severe adverse events, the therapy was de-escalated to trastuzumab monotherapy after six months of treatment. Initial restaging revealed partial response after the combination therapy of FLOT with trastuzumab. After reduction to trastuzumab monotherapy, the disease remained stable for two years until radiological complete response was observed. Trastuzumab monotherapy was continued for another two years to maintain complete response. Eleven months after the discontinuation of the therapy, no recurrence of the disease was detected. In conclusion, complete response can be achieved under trastuzumab monotherapy in exceptional responders.
Gesehen am 11.02.2020